Physicochemical and Sensory Properties of Cookies Produced from Wheat and Tigernut (Cyperus esculentus) Flour Blends - Igbabul, Bibiana Dooshima; Ishaleku, Daniel; Tersoo-Abiem, Evelyn Mnguchivir (European Journal of Applied Sciences, 2024)
Cookies were produced from the composite flour of wheat and tigernut (yellow and black variety). Five samples were produced, namely samples A-E. Sample A (control) – 100% wheat flour; samples B – 70% wheat and 30% yellow tigernut flour; sample C – 70% wheat and 30% black tigernut flour; sample D – 50% wheat and 50% yellow tigernut and sample E – 50% wheat and 50% black tigernut flour. The spread ratio for the yellow tigernut cookies (i.e sample E) was 1.44mm and that of the black variety of tigernut was 1.44mm. These differed significantly (p>0.05) from the control (i.e sample A), which had spread ratio of 1.34mm. The protein content of sample E was 15.63% while sample D had 9.57%. Sample C had 9.83% fat while sample B had 8.33% fat. These showed that the black variety of tigernut contains higher amount of protein and fat. The phytate content of the yellow variety supplementation of tigernut cookies produced from wheat flour supplemented with of tigernut (i.e samples B and D) were 0.34 and 0.61 mg/100g respectively, while that of the black variety supplementation of tigernut cookies (i.e samples C and E) were 0.71 and 0.82 mg/100g respectively. There was significant difference (p>0.05) between these two varieties. Calcium content for the black variety cookies were 176.34 and 208.82 mg/100g while that of the yellow variety were 102.43 and 132.66 mg/100g. Good organoleptic qualities were observed for both varieties and the control sample since they all had values higher than five (which is the minimum acceptable value on the nine point hedonic scale). However the control sample was generally the most acceptable. The formulated cookies (yellow and black variety) competed fovourably with the 100% wheat flour cookies.